Measurement of the Yield Ratio of the \(^122m,gSb\) Isomeric Pair Above the Giant Resonance - Khue, Pham Duc; Thanh, Kim Tien; Do, Nguyen Van (Communications in Physics, 2012)
The yield ratio of the high-spin state of \(^122mSb (8^ - )\) and the low-spin state of \(^122gSb (2^-)\) formed via the \(^123Sb(γ, n)^122m,gSb\) reaction has been measured as a function of the bremsstrahlung end-point energy in the range of 40-MeV to 60-MeV. Use was made of the activation technique in combination with high-resolution \(γ\)-ray spectrometry. The isomeric yield ratios for the \(^123Sb(γ,n)^122m,gSb\) reaction measured at 40-, 45-, 50-, 55-, and 60-MeV bremsstrahlung are \(0.341± 0.022\), \(0.362 ± 0.020\), \(0.374 ± 0.021\), \(0.371 ± 0.021\), and \( 0.367 ± 0.022\). According to our knowledge, the present results are the first measurement.